Wakaf Sumur Yayasan Aksi Cepat Tanggap (Act): Analisis Kontributif Wakaf Sumur Dalam Mengatasi Krisis Air Bersih Di Kecamatan Gandus - Citra Pertiwi; Citra Lestari; Julia Julia (Prodi Manajemen Zakat dan Wakaf Fakultas Ekonomi dan Bisnis Islam, 2024)
Abstract: The dry season drought causes problems for the community, especially the acquisition of basic needs, namely water. The drought causes a clean water crisis among the community, especially in remote villages that are not covered by the PDAM. Villages that only get water from dug wells cannot expect anything if the drought has come. The Islamic instrument related to the water crisis is the waqf well located in Pulokerto Village. This journal is elaborated with two problem formulations including (a) How is the Well Waqf Mechanism by the Aksi Cepat Tanggap (ACT) Foundation? (b) How is the Contribution of the Waqf in Overcoming the Clean Water Crisis in Gandus sub-district. This is a field research with descriptive qualitative research method. Data collection methods with observation, interviews and documentation. In this study, the object of research is the contribution of waqf wells in Gandus District with purposive sampling technique. Purposive sampling is a data source sampling technique with certain considerations. The data analysis techniques used in this research are source triangulation, method triangulation (interviews, observation and documentation) and time triangulation. Where this research resulted in several things, namely, the contribution of waqf wells by the Aksi Cepat Tanggap Foundation is one of the programs that provides solutions to the problems faced by the people of Pulokerto Village, Gandus District against the clean water crisis. The contributions of waqf wells include waqf wells for Islamic boarding schools, waqf wells for mosques and waqf wells for villages